Toxicities of microplastic fibers and granules on the development of zebrafish embryos and their combined effects with cadmium. (April 2021) - Cheng, Haodong; Feng, Yifan; Duan, Zhenghua; Duan, Xinyue; Zhao, Shuang; Wang, Yudi; Gong, Zhiyuan; Wang, Lei
Abstract: Toxicity of microplastics (MPs) in granular form to aquatic animals has been frequently tested, whereas the effects of fibrous MPs remain further explored. In this study, the effects of polyethylene terephthalate granular particles ( p -PET, approximately 150 μm in diameter) and fibers ( f -PET, approximately 3–5 mm in length and 20 μm in diameter) on the development of zebrafish embryos and their joint effects with cadmium (Cd) were compared. p -PET and f -PET accelerated the velocities of blood flow and heart rate and inhibited hatching in zebrafish embryos because of their barrier effects on the channels in the embryonic chorion and enhanced the mechanical strength of the chorion. The Cd content in the chorion increased by p -PET due to the adsorption of p -PET on the chorion. By contrast, more f -PET dissociated in culture medium and resulted in low Cd content in the chorion. Given that chorion can effectively block p -PET and f -PET, the Cd accumulation in eggs significantly decreased ( p < 0.05) under p -PET/ f -PET and Cd combined treatment because of the reduction in the bioavailability of Cd. Therefore, p -PET and f -PET decreased the toxicities of Cd on all the target endpoints in this study, and the detoxification effect of f -PET at 72 hpf was more significant than that of p -PET. These results suggest that the toxicity induced by MPs might be form-related. Graphical abstract: Image 1 Highlights: PET fibers and granules have affinities with zebrafish embryonic chorion. PET fibers or granules inhibited the embryonic development of zebrafish. PET granules adsorbed more Cd in the chorion and reduced Cd content in eggs. PET fibers were more significant in decreasing Cd toxicity than PET granules.